THREE-DIMENSIONAL THERMAL STRESSES IN A SOLID ELASTIC CYLINDER OF FINITE LENGTH - Токовий, Юрій Владислович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
An analytical technique for solution of the three-dimensional thermoelasticity problem for a solid elastic cylinder of finite length with force-free boundary is presented. By making use the thermal potential technique, the original problem of thermoelasticity is reduced to the corresponding elasticity problem for the cylinder exposed to force loadings on its plane and cylindrical boundaries. To solve the obtained problem, we employ the method of cross-wise superposition.